Exorcist the beginning - Harlin, Renny; Wisher, William; Carr, Caleb (Warner Home Video, 2005)
Mr. Merrin, a lapsed Catholic priest is summoned to East Africa in 1949 to retrieve a demonic idol. He discovers a buried church, a vast underground cavern, demonic possession, and a legacy of carnage that preys upon guilt- ridden memories from his parish in Nazi-occupied Holland.